A fatigue and stress distribution analysis of horizontal axis wind turbine blade - Gurmesa, Fakada D.; Santhosh, Johnson A.; Biniyam A., Biniyam A.; Kassaye, Firew T.; Kedir, Yahiya A. (Asia-Pacific Journal of Science and Technology, 2022)
Fatigue stress distributions developed on the wind turbine lead to fatigue failure due to various loads. The present study was performed under various loads such as gravitational load, centrifugal forces, and aerodynamic forces (lift and drag pressure) for Horizontal-Axis Wind Turbine (HAWT) blade made of composite materials (E-glass fibre). Fatigue failure analysis of wind turbine blade type the National Advisory Committee for Aeronautics (NACA) 4412 performed under wind speed of 35 m/s. After completing both the Computational Fluid Dynamics (CFD) and static structural analysis, the output results such as total stress, deformation, and shear stress are identified. Simultaneously, critical locations on the blade are shown on the CFD results. It is concluded that the maximum stress location in a wind turbine is the blade’s leading edge and the blade root (part the nearer of the hub). The wind speed increases beyond recommendation design, and it decreases the life of the wind turbine blade. The blade’s leading edge is more deformed, and the centrifugal load is considered the most influential factor in the life of the blades.